PROSES DIFUSI INOVASI E-AGRIBUSINESS : REGOPANTES PADA END-USER KOMODITAS PERTANIAN DI JABODETABEK - Eki Yoan Meydora (Prodi Ilmu Komunikasi Universitas Putera Batam, 2019)
This study analyzes the information dissemination process of RegoPantes, an e-agribusiness innovation to connect farmers to agricultural commodity users directly, thus cutting the long chain of distribution. RegoPantes is a platform developed by 8villages to help farmers receive fair price for every agricultural commodity they sell, with the aim to help improve the farmer welfare. The purpose of this study is to identify constraints faced by diffusion agencies that disseminate information about RegoPantes to the public specifically housewives as end users of agricultural commodities. This study uses descriptive qualitative methods to provide an in-depth understanding of the diffusion of RegoPantes. Data was collected through in-depth interviews and document studies. Based on the result of research known that 8villages chose a public relations approach that included press relations in disseminating information about RegoPantes. Although there have been many publications from various media, the adoption of innovations by end users of agricultural commodities is still not optimal.